Antecedents of organizational citizenship behavior / Hafizah Mohd Yamin - Mohd Yamin, Hafizah (2014)
The research entitled "Antecedents of Organizational Citizenship Behavior'' was chosen for this study. This research was carried out to study on the antecedents of organizational citizenship behavior which is job satisfaction, perceive organizational support, organizational commitment, leadership, and empowerment among employee in Majlis Daerah Segamat. The introduction of the study as a whole, it is contains the background of the study, problem statement, research questions, research objectives, scope of the study, significance of the study, limitation and definition of key terms. 150 questionnaires have been distributed to employees at Majlis Daerah Segamat. For literature review, the researcher refers on previous journal and articles. It can identify whether the independent variables used have an influence towards the dependent variables. It also explained definition of each variable, theoretical framework and hypothesis. In the research, descriptive research has been conducted. Primary and secondary data were applied. Besides that, convenience sampling has been used as research design and also used table to determine sample size. Hypothesis testing also included in this chapter. All results and analysis were explained in this chapter. For the conclusion was divided based on the finding and the recommendation, researcher have provide several way that can be taken by organization in order to improve employees organizational citizenship behavior. The result for the research, only four variables are significant with OCB which is job satisfaction, organizational commitment, empowerment and leadership. While for perceive organizational support are not significant with OCB.